Late onset Leber's optic neuropathy: a case confused with ischaemic optic neuropathy. - Borruat, F X (1992)
A case is reported of a 63-year-old man with progressive central visual loss in one eye followed 11 months later by involvement of the fellow eye. A diagnosis of chronic ischaemic optic neuropathy was considered. However, despite a negative family history, the absence of electrocardiographic abnormalities, and minimal fundus changes a diagnosis of Leber's optic neuropathy was made on the basis of magnetic resonance imaging findings and the mitochondrial DNA mutation at base pair 11778.